2001
DOI: 10.1016/s0009-2614(01)00343-8
|View full text |Cite
|
Sign up to set email alerts
|

The observation of fluorescence from excited states of NF2 and NF following the photodissociation of NF3 in the 11–30 eV range

Abstract: A study of the vacuum-ultraviolet (VUV) fluorescence spectroscopy of NF 3 in the 11-30 eV range is presented. Synchrotron radiation from BESSY1, Berlin provides the VUV excitation source. Emission due to NF bΣ -at 528.8 nm is observed between 11.5 and 21.0 eV.Other emissions, which are believed to be due to transitions between highly excited states of NF 2 , are observed at higher energies, 14.8-24.5 eV. Lifetimes associated with two of these bands at 325 nm and 410 nm are determined to be 12.9 and 13.0 ns, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Born corrections to the electron-impact excitation cross sections were used to account for long range dipole effects 42,43 . Hamilton et al 25 estimated the products of the dissociation process by analogy with the observed photodissociation cross sections of Seccombe et al 44 which suggested that the following process can occur:…”
Section: Vibrational Excitation Cross Sectionsmentioning
confidence: 99%
“…Born corrections to the electron-impact excitation cross sections were used to account for long range dipole effects 42,43 . Hamilton et al 25 estimated the products of the dissociation process by analogy with the observed photodissociation cross sections of Seccombe et al 44 which suggested that the following process can occur:…”
Section: Vibrational Excitation Cross Sectionsmentioning
confidence: 99%
“…The molecular structure of N 2 F 4 has been reported from microwave rotational spectroscopy studies. , The rotational spectrum of the NF 2 free radical in the millimeter-wave region and its microwave and absorption spectra have been reported. The photodissociation of NF 3 has been studied by vacuum-ultraviolet fluorescence spectroscopy . The crystal structures of several N 2 F + and NF 4 + salts have been reported. ,, The structure of the free gaseous ion N 2 F + has also been determined using millimeter-wave spectroscopy .…”
Section: Introductionmentioning
confidence: 99%
“…The observed excimer bands apparently belong to the desorbed excited fragments illustrating the importance of the excited-state stimulated desorption processes in cryogenic solids. Relatively weak spectral features at 3.65 eV and 3.15 eV do not correspond to the known NF 3 fluorescence products [26]. They indicate that a part of the expulsed excited products is hot and possess significant vibrational excitation: corespondingly v' = 2-3 (B-state) and v' = 6 ± 1 (C-state).…”
Section: Ionic Chromophores Xe P + (P £ 4) In Multishell Rare-gas Clumentioning
confidence: 89%